PENGARUH BAHAN PENGEKSTRAK TERHADAP KARAKTERISTIK EKSTRAK SENYAWA FUNGSIONAL DARI KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) - Nana Sutisna Achyadi (Department of Food Technology, Universitas Pasundan, Bandung, 2019)
The purpose of this study is to determine the use of extracting materials suitable for dragon fruit skin extraction so that the functional compound (anthocyanin) obtained optimally. The research method consisted of preliminary research and main research. Preliminary research was conducted to determine the maceration method (maceration and maceration modification with agitator) to be used in the main research and raw material analysis. The main research is conducted to determine the appropriate extracting agent (various types of acids and mixtures). The experimental design used in the study was Randomized Block Design (RAK) with 1x6 factorial pattern with 4 replications. Response variable in this research is physical response include analysis of dye and calculation of rendement and chemical response which include determination of acidity level (pH), vitamin C content analysis, water content analysis, and antioxidant activity analysis. The result of preliminary research is obtained that the maceration method chosen is the usual maceration method and the result of raw material analysis which includes the vitamin C level of 184,937 mg vitamin C / 100 gram sample; analysis of dye where L * 37.56 a * 9.29 b * -0.31; and acidity level (pH) 4.73. While based on the results from the main study obtained that the selected extracting material is 2% tartrate (w / v). Response result obtained that is yield 19,09%; dye analysis with L* 48,12 a * 31.02 and b * 2,70; acidity level (pH) 0.73; rate of water 6,3%; vitamin C levels of 167.63 mg vitamin C / 100 gram samples; as well as antioxidant activity of 10,242.83 ppm.